Pemberdayaan Pemuda Karang Taruna Melalui Pemanfaatan Keterampilan Massage Kebugaran Berbasis Aplikasi Android - Purnomo, Ardhi Mardiyanto Indra; Hanief, Yulingga Nanda; Pamungkas, Danar Putra (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2019)
Often people experience fatigue as a result of daily activities, but none of them took the initiative to restore their fitness through fitness message. The youth of Karang Taruna in Ngulankulon Village and Ngulanwetan Village, Pogalan District, Trenggalek Regency has strong potential to develop skills in the field of fitness message. The young people who are members of Karang Taruna members are dominated by people who are not economically productive. Most young people experience dependence on smartphones. Young people have not been able to use smartphones for positive activities. Therefore, empowerment is needed for youths of Ngulankulon Village and Ngulanwetan Village to develop communities that can be independent in the health sector, so that they can make a real contribution to the development of integrated fitness massage skills by applying science and technology towards positive things in community life. Empowerment is implemented in the form of Android-based fitness massage training. The method applied is Participatory Learning and Action (PLA). This method succeeded in increasing knowledge and fitness massage skills for trainees. The results of the pretest showed the participants' level of understanding was 66%, while after taking part in the training and mentoring, posttest was conducted with the result of an understanding level of 89%. The data shows an increase in fitness massage skills for youth youth.